KETELADANAN GURU AGAMA ISLAM DALAM MEMBENTUK AHLAK KARIMAH SISWA : Penelitian di Madrasah Aliyah Se-KKM MAN 3 Cianjur - Kamaludin Kamaludin (STAI Pelabuhan Ratu, 2020)
The purpose of this study was to identify and analyze exemplary values, implementation, results, supporting and inhibiting factors, from the application of exemplary values ​​of Islamic Religion teachers in shaping good morals in Madrasah Aliyah Negeri as KKM MAN 3 Cianjur. This research uses a qualitative approach with descriptive methods. The data collection techniques are observation, interview, and documentation. So that the data collected is analyzed using data reduction steps, data display and data inclusion. The results showed that with the application of exemplary teacher can improve and can shape the al-karimah morals of students at Madrasah Aliyah Negeri 3 and MA Al-Falah Cianjur.